2016
DOI: 10.1071/sh16049
|View full text |Cite
|
Sign up to set email alerts
|

Self-testing for Trichomonas vaginalis at home using a point-of-care test by women who request kits via the Internet

Abstract: We offered a point-of-care test for Trichomonas vaginalis to women via the Internet to determine if it was acceptable to women to perform the test at home. Most of the 102 participants felt that it was easy to collect the specimen, follow the instructions, and read and interpret the results for the trichomonas self-testing assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
(4 reference statements)
0
14
0
Order By: Relevance
“…Additionally, women have been enrolled in a research study to perform the OSOM assay themselves at home after ordering a home TV test kit via the internet; they obtained accurate results compared with a mailed-in NAAT assay and found the home test to be highly acceptable 30. Use of this assay as a standard of care POC test for the detection of trichomoniasis in an emergency department was also shown to prevent overtreatment of vaginal infections compared with historical controls before the introduction of the POC test, resulting in good antibiotic stewardship 31…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, women have been enrolled in a research study to perform the OSOM assay themselves at home after ordering a home TV test kit via the internet; they obtained accurate results compared with a mailed-in NAAT assay and found the home test to be highly acceptable 30. Use of this assay as a standard of care POC test for the detection of trichomoniasis in an emergency department was also shown to prevent overtreatment of vaginal infections compared with historical controls before the introduction of the POC test, resulting in good antibiotic stewardship 31…”
Section: Methodsmentioning
confidence: 99%
“…Although STIs are most prevalent in people aged 16-29 years, recent studies have suggested an increased rate in people over 30 years [25]. Furthermore, despite the finding that people who met partners on dating websites and apps were more likely to have had an STI test in the last year, a substantial proportion of respondents who reported having sex with someone they met online (likely to be a new sexual partner) reported not having an STI test in the past year, suggesting an opportunity to raise awareness about STI testing further and to use targeted advertisements to direct people to easy access points such as new websites where pathology request forms can be downloaded without attending a clinic [26]. Some have also suggested that these platforms have the capacity to enable partner notification and data collection in relation to sexual health [27].…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the performance and acceptability of selfcollecting genital samples are high. 9,[13][14][15][16][17][18][19][20] Women report self-collection of vaginal samples to be easy and convenient, both in the clinical setting and at home and women are likely to choose self-collected vaginal swabs over sample collection during a pelvic exam. [13][14][15]20 Reports comparing self-collected penile swabs to first catch urine collected at home or in the clinic have shown self-collected penile swabs performance is equal to or better than first catch urine.…”
Section: Discussionmentioning
confidence: 99%
“…9,[13][14][15][16][17][18][19][20] Women report self-collection of vaginal samples to be easy and convenient, both in the clinical setting and at home and women are likely to choose self-collected vaginal swabs over sample collection during a pelvic exam. [13][14][15]20 Reports comparing self-collected penile swabs to first catch urine collected at home or in the clinic have shown self-collected penile swabs performance is equal to or better than first catch urine. 16,17 A recent comparison of self-collected glans/meatal dry swabs, clinician-collected urethral swabs, and first catch urine for CT/GC testing showed that selfcollected glans/meatal dry specimens had a high agreement with clinician-collected specimens and sensitivity and specificity adequate for use in screening programs.…”
Section: Discussionmentioning
confidence: 99%